REKONSTRUKSI SISTEM PENDIDIKAN PESANTREN SALAFI DI ERA MODERN - amelia, ida; Astuti, Reni; Zainal Mutaqin, Mumu; Arifin, Muhammad (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
This research aims to dig deeper into the reconstruction of the Salafi Islamic boarding school education system in the face of global challenges and modernization, the education system implemented by kiai and educators in salafi Islamic boarding schools must be created to be able to follow the flow of change. The challenges and opportunities brought by globalization must be faced by Islamic boarding schools wisely. So that it can ensure that Islamic boarding school graduates can compete in the global community. The research method used in this study is a descriptive method with a qualitative approach. The data collection technique used is a literature study, which is to review various literature, both in the form of books and scientific articles, related to research topics. The things that need to be reconstructed from the salafiyah pesantren education system to catch up in facing the demands of change in the midst of the rapid flow of modernization and globalization include, 1) changing the leadership pattern/paradigm from charismatic to rationalistic and from authoritarian-paternalistic to diplomatic, 2) improving the curriculum structure with a more broad orientation, 3) changing the scientific paradigm of pesantren from a verbalistic approach and dogmatic to a critical and innovative attitude, 4) making business activity and skills education programs, 5) facilitating access to media and information about the development of the times.